ANALISIS APLIKASI DIGITAL DALAM MENINGKATKAN EFISIENSI PENGELOLAAN KEUANGAN UMKM PENDEKATAN TOE MODEL (STUDI KASUS BENGKEL SIMPATI MOTOR) - Izah Ardina Putri; Zahara Zahara; Josephine Sudiman (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the role of digital applications in improving the efficiency of financial management in MSMEs using the TOE (Technology-Organization-Environment) Model approach. The research explores the benefits of using digital applications in influencing financial management efficiency, as well as the advantages of organizational readiness in implementing digital tools to enhance financial processes. This research adopts a qualitative approach. Data collection methods include participant observation and in-depth interviews. Sources of data are obtained from all relevant parties through participation, documentation, observation, or interviews. The selected research object is a micro-enterprise, Bengkel Simpati Motor. Based on the findings, the use of digital applications at Bengkel Simpati Motor provides relative advantages in financial management efficiency, particularly in terms of time and cost, by enabling faster record-keeping and reducing the need for paper and accounting books. Organizational readiness, including both infrastructure and human resources, supports the successful implementation of the digital system, with strong support from within the company.